Religious Diversity and the Number of Religious Parties Around the World. Issue 2 (3rd April 2019) - Raymond, Christopher D.
ABSTRACT: Arguing that religious diversity creates incentives for political cooperation, recent research questions the assumption that religious diversity leads to more fragmented party systems and finds a negative association between religious diversity and the fragmentation of vote shares. Before this revisionist perspective can be believed, however, we need to observe the causal processes linking religious diversity and party system fragmentation. One of these is that religious diversity is negatively associated with the number of religious parties contesting elections. Using data counting the number of religious parties in elections around the world between 2011 and 2015, the analysis shows that religious diversity is negatively associated with the number of religious parties. In line with the revisionist perspective, these results suggest that religious diversity creates incentives for political cooperation that lead elites to cooperate across religious group lines in support of parties representing their shared political interests.